Enhanced inflammatory cell profiles in schistosomiasis-induced pulmonary vascular remodeling. (February 2017) - Ali, Zahara; Kosanovic, Djuro; Kolosionek, Ewa; Schermuly, Ralph T.; Graham, Brian B.; Mathie, Alistair; Butrous, Ghazwan
Schistosomiasis (bilharzia) is a neglected parasitic disease caused by trematode flatworms of the genus Schistosoma which affects over 240 million people worldwide. It is characterized by the formation of inflammatory granulomas around deposited parasite eggs. Recent studies have revealed that immune and inflammatory responses play a crucial role in pathogenesis of schistosomiasis. The aim of this paper is to systematically evaluate the number and distribution of inflammatory cells in S. mansoni -infected mice at different doses and time points. Immunohistochemistry was performed on lung and liver tissue sections from Schistosoma -infected mice and uninfected healthy controls. Positively stained cells in whole-lung/liver tissue sections, surrounding the eggs, and in the different compartments of the tissues, were counted. We found a significant increase in the number of mast cells (toluidine blue + ), CD3 + cells, CD14 + cells, CD68 + cells, and CD15 + cells in Schistosoma -infected tissues compared with untreated healthy controls ( P ≤ 0.05 for all). Our findings revealed altered and enhanced immune cell infiltration in schistosomiasis. We suggest that these cells may contribute to the pathophysiology of Schistosoma resulting in pulmonary vascular remodeling.